Monatomic Sn-doped ZnO-based gas sensitive material as well as preparation method and application thereof
Single-atom Sn-doped ZnO nanosheets derived from metal-organic frames solve the problems of low sensitivity and poor selectivity of sensing materials, achieve high response and good selectivity to trace acetone gas, and provide new sensing Material design ideas.
Patent Information
- Application Number
- CN202411244798.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-02
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
The existing semiconductor metal oxide sensing materials have low sensitivity and poor selectivity, and are uneven doping sites and are prone to agglomeration. The morphological regulation methods are limited, making it difficult to improve gas sensing activity.
Single-atom Sn-doped ZnO nanosheets derived from metal-organic frames are used to self-assemble and calcinate through environmentally friendly mechanochemical self-assembly and calcinate, so that Sn is uniformly distributed in the ZnO crystal in the form of a single atom to form an interwoven nanosheet morphology. Improve the adsorption and catalytic decomposition capabilities of gas molecules.
It achieves high response and good selectivity to trace acetone gas, has low detection limit, is suitable for the development of acetone gas sensors, and has potential for diabetes diagnosis, providing new ideas for structural regulation of semiconductor oxide materials.
Smart Images

Figure CN119118186A_ABST
Abstract
Description
(I) Technical field:
[0001] The present invention relates to the technical field of metal oxide material preparation, and particularly to a metal-organic framework derived single-atom Sn-doped ZnO nanosheet, a preparation method and application thereof, and a gas molecule detection application thereof, namely, a single-atom Sn-doped ZnO-based gas-sensitive material and a preparation method thereof. (II) Background technology:
[0002] In social production activities, a large amount of industrial raw materials are needed. These industrial raw materials contain a large number of volatile organic compounds (acetone, methanol, ethanol, etc.). If these volatile organic compounds are inhaled into the human body, they will cause irreversible damage to the health of the body; social production will also emit a large amount of toxic and harmful gases (ammonia, formaldehyde, nitrogen oxides, etc.), which will also have a destructive effect on the atmospheric environment; on the other hand, the exhaled breath of the human body contains a large number of biomarker gases (acetone, ammonia, methanol, etc.), and the concentration level of these gases in the exhaled breath is closely related to the occurrence of some diseases. Therefore, it is very necessary to realize the concentration detection of various gases through specific devices for environmental protection, health monitoring, disease diagnosis, etc. Gas sensor technology is such a device for detecting various types and concentrations of gases. According to different detection principles, gas sensors are divided into many categories, among which chemical resistance sensors with semiconductor metal oxides as sensing materials are the most widely used because they have the characteristics of low manufacturing cost, small size, and strong designability. In response to the problems of poor sensitivity, low detection limit, and poor selectivity faced by current semiconductor-based resistive sensors, researchers have developed methods such as doping and morphology control to improve the activity of sensing materials. Moderate doping can bring about surface defects and active sites, and good morphology can expose the material surface to the greatest extent; however, current doping methods face problems such as uneven doping sites and easy agglomeration of doping sites; known morphology control methods are also limited, so it is necessary to develop new doping and morphology control methods to improve the sensing activity of materials.
[0003] Metal-Organic Frameworks (MOFs) materials are a type of framework materials formed by self-assembly of metals / metal clusters and organic ligands through coordination. They have the characteristics of composition / structure adjustability, high porosity, high specific surface area, etc., and are widely used in catalysis, adsorption separation, sensing and other fields. The gas adsorption and separation characteristics of MOFs materials make them have great potential in the field of gas sensing; however, MOFs materials themselves have poor conductivity and are difficult to be directly used as sensing active materials; derivative materials with MOFs as precursors have moderate conductivity and inherit the porous characteristics and specific morphology of the precursors to a certain extent, making them very suitable for use as sensing materials. By constructing bimetallic MOFs and further calcining them into oxides, the second metal can often form a uniform doping phase; by regulating the morphology of MOFs precursors, the derivatives can often form well-defined microscopic morphologies. (III) Summary of the invention:
[0004] The purpose of the present invention is to provide a single-atom Sn-doped ZnO-based gas-sensitive material and a preparation method and application thereof, namely, a single-atom Sn-doped ZnO nanosheet derived from a metal organic framework and a preparation method thereof, which can solve the problems of poor activity and low sensitivity of semiconductor metal oxide sensing materials and limited conventional performance control methods. The present invention discloses a method for improving the gas-sensing ability of the sensing material. The present invention adopts an environmentally friendly mechanochemical method to complete the self-assembly of bimetallic MOFs, and a MOFs precursor is transformed into a microstructure and morphology through a simple solvent treatment. The effect of the MOFs framework during calcination is utilized to allow Sn to be doped into the ZnO crystal structure in the form of a single atom, and finally a single-atom Sn-doped ZnO-based gas-sensitive material is formed, which presents an interwoven nanosheet morphology, and exhibits high response and good selectivity to trace amounts of acetone gas, thereby providing a new idea for the development of acetone gas sensors.
[0005] The technical solution adopted by the present invention is: a single-atom Sn-doped ZnO-based gas-sensitive material, characterized in that it is derived from a metal-organic framework and has the morphology of interwoven nanosheets with a diameter of 500-700nm and a thickness of 30-50nm; Sn is doped into the ZnO crystal structure in the form of a single atom during the calcination process, and a large number of evenly distributed Sn active sites are beneficial to the adsorption and catalytic decomposition of gas molecules.
[0006] The single-atom Sn-doped ZnO-based gas-sensitive material uses zinc oxide powder (ZnO), divalent tin salt, terephthalic acid (H2BDC), and N,N-dimethylformamide (DMF) as raw materials, obtains a metal-organic framework precursor through an environmentally friendly mechanochemical method, and then realizes the structural and morphological transformation of the MOF precursor through a simple solvent treatment process, and finally obtains a single-atom Sn-doped ZnO nanosheet by calcination.
[0007] The divalent tin salt is SnCl2·2H2O.
[0008] A method for preparing a single-atom Sn-doped ZnO-based gas-sensitive material comprises the following steps:
[0009] (1) Synthesis of Sn / Zn-MOF-B: Zinc oxide powder (ZnO), divalent tin salt, terephthalic acid (H2BDC), and N,N-dimethylformamide (DMF) solvent were mixed and ball-milled into a dry and fine white powder to prepare the bimetallic MOF precursor Sn / Zn-MOF-B;
[0010] (2) Synthesis of Sn / Zn-MOF-L: ① The prepared Sn / Zn-MOF-B was placed in a DMF solution, subjected to ultrasonic treatment, centrifuged using a centrifuge, the bottom solid was separated, and the solution was placed in DMF again for ultrasonic treatment, and the above process was repeated at least 3 times; ② The DMF-treated solid was placed in an ETOH solution, subjected to ultrasonic treatment, centrifuged using a centrifuge, the bottom solid was separated, and the solution was placed in ETOH again for ultrasonic treatment, and the above process was repeated at least 3 times to obtain the bimetallic MOF precursor Sn / Zn-MOF-L;
[0011] (3) Synthesis of single-atom Sn-doped ZnO: The prepared Sn / Zn-MOF-L precursor was calcined under air to obtain single-atom Sn-doped ZnO gas-sensitive material.
[0012] The molar ratio of Sn to Zn in the solid raw material of step (1) is 2% to 10%.
[0013] The molar ratio of Zn to H2BDC in the solid raw material of step (1) is 1:1 to 1:2.
[0014] In the step (1), the mass ratio of the solid raw material to the DMF solvent is 3:1 to 2:1.
[0015] In the step (1), ZnO powder, H2BDC, SnCl2·2H2O and DMF solvent are placed in a ball mill, the ball mill is fixed on a three-dimensional swing ball mill, and ball milling is performed at a rotation speed of 1200 rpm for 40 to 50 minutes.
[0016] In the step (2), the prepared Sn / Zn-MOF-B is placed in a DMF solution and subjected to ultrasonic treatment for 1 to 2 minutes; the solid is separated from the bottom by centrifuging at a speed of 8000 to 10000 rpm for 4 to 6 minutes, and the solid is re-placed in DMF for ultrasonic treatment, and the process is repeated 3 times; the solid treated with DMF is placed in an ETOH solution and subjected to ultrasonic treatment for 5 to 10 minutes; the solid is separated from the bottom by centrifuging at a speed of 8000 to 10000 rpm for 4 to 6 minutes, and the solid is re-placed in ETOH for ultrasonic treatment, and the process is repeated 3 times to obtain a bimetallic MOF precursor Sn / Zn-MOF-L.
[0017] In the step (3), the Sn / Zn-MOF-L precursor is placed in a ceramic ark and heated and calcined in a tubular furnace.
[0018] In the step (3), the Sn / Zn-MOF-L precursor is calcined at 450-500° C. for 2-3 hours.
[0019] A method for preparing a gas sensor based on a single-atom Sn-doped ZnO-based gas-sensitive material, the steps of which are as follows:
[0020] (1) 3-8 mg of single-atom Sn-doped ZnO-based gas-sensitive material is put into 0.5-1 ml of ethanol, and ultrasonic treatment is performed to form a uniform suspension. The suspension is then aspirated and dropped onto two gold electrodes on the surface of an alumina ceramic plate to form a sensor;
[0021] (2) The sensor drop-casted with the gas-sensitive material is aged for 1 to 3 days in an environment with a bias voltage of 4 V to obtain a gas sensor based on a single-atom Sn-doped ZnO-based gas-sensitive material.
[0022] In the step (1), the single-atom Sn-doped ZnO-based gas-sensitive material is placed in ethanol and ultrasonically treated for 20 to 30 minutes to form a uniform suspension. The suspension is sucked using a 1 mL syringe and a drop is squeezed out and dropped on two gold electrodes separated from each other and with a spacing of 0.2 mm on the surface of an alumina ceramic plate (1 mm×1.5 mm). The dropping is repeated 3 to 5 times to form a sensor.
[0023] The single-atom Sn-doped ZnO-based gas-sensitive material is applied to the detection of trace gases.
[0024] The gases are acetone (CH3COCH3), formaldehyde (HCHO), methanol (CH3OH), and ethanol (CH3CH2OH).
[0025] Acetone (CH3COCH3), formaldehyde (HCHO), methanol (CH3OH), and ethanol (CH3CH2OH) were detected at 270-310°C.
[0026] Based on the above scheme, compared with the prior art, the advantages of the present invention are:
[0027] (1) An environmentally friendly mechanochemical method was used to synthesize MOFs precursors. The morphology of the MOFs precursors was transformed through simple solvent treatment to achieve a good lamellar morphology. After calcination, single-atom Sn-doped ZnO nanosheets with a diameter of 500-700 nm and a thickness of 30-50 nm were finally obtained.
[0028] (2) In the single-atom Sn-doped ZnO-based gas-sensitive material obtained by the present invention, Sn is doped into the crystal structure of ZnO in the form of a single atom. This doping is very uniform, so that the active sites are exposed to the greatest extent. The doping sites have a strong adsorption effect on acetone molecules, so that the single-atom Sn-doped ZnO gas-sensitive material exhibits an ultra-high response (R 0.04) to trace acetone gas (10 ppm). a / R g =213), ultra-low detection limit (0.52ppb), and good selectivity compared to other gases (formaldehyde, methanol, ethanol, etc.). The response values of single-atom Sn-doped ZnO gas-sensitive materials to 10ppm formaldehyde, 10ppm methanol, and 10ppm ethanol are 23.5, 53.2, and 96.7, respectively.
[0029] (3) The single-atom Sn-doped ZnO-based gas-sensitive material obtained in the present invention has the potential to achieve painless diagnosis of diabetes by detecting the concentration of acetone gas in the exhaled breath of the human mouth, and has good application prospects.
[0030] (4) The preparation method adopted by the present invention is simple to operate, low in cost, and environmentally friendly, and provides a new idea for the design of highly active gas-sensitive materials and the structural regulation of semiconductor oxide materials. (IV) Description of the drawings:
[0031] Figure 1 The polycrystalline powder diffraction (PXRD) pattern of Sn / Zn-MOF-B prepared in Example 2;
[0032] Figure 2 The polycrystalline powder diffraction (PXRD) pattern of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2;
[0033] Figure 3 X-ray photoelectron (XPS) spectrum of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2;
[0034] Figure 4 This is a scanning electron microscope (SEM) image of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2;
[0035] Figure 5 This is a transmission electron microscope (TEM) image of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2;
[0036] Figure 6 This is a response-operating temperature diagram of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2 to 10 ppm acetone gas at 270-310° C.;
[0037] Figure 7 This is a response-time diagram of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2 to 10 ppm acetone gas at 290° C.;
[0038] Figure 8 The graph is a response-concentration diagram of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 2 to acetone gas of different concentrations at 290°C;
[0039] Fig. 9 This is the response-gas type diagram of the single-atom Sn-doped ZnO-based gas-sensitive material prepared in Example 3 to different gases (10 ppm) at 290°C. (V) Specific implementation methods:
[0040] The present invention is further described below in conjunction with specific embodiments.
[0041] Example 1: 1.5mmol ZnO, 0.06mmol SnCl2·2H2O, 3mmol H2BDC and 200μL DMF were put into a nylon ball mill, fixed to a three-dimensional swing ball mill, and ball milled at 1200rpm for 45min. The solid powder in the ball mill was collected to obtain the bimetallic MOF precursor 4% Sn / Zn-MOF-B. It was placed in a 30mL DMF solution for ultrasonic treatment for 1 minute. Then, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the DMF solution for ultrasonic treatment, and repeated 3 times. The DMF-treated sample was placed in a 30mL ETOH solution for ultrasonic treatment for 5 minutes, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the ETOH solution for ultrasonic treatment, and repeated 3 times. The solvent-treated solid product was dried to obtain a bimetallic MOF precursor 4% Sn / Zn-MOF-L. The prepared 4% Sn / Zn-MOF-L was placed in a ceramic ark, and then the ceramic ark was placed in a tube furnace to heat the MOF precursor in an air atmosphere at a heating rate of 2°C / min. The temperature was raised to 500°C and maintained at 500°C for 150 minutes. After cooling, a single-atom Sn-doped ZnO-based gas-sensitive material (4% Sn-doped ZnO) was obtained. 5 mg of 4% Sn-doped ZnO solid powder was taken and put into 0.5 mL ETOH solution, and the dispersion was ultrasonically treated for 30 minutes to form a white suspension. The suspension was aspirated with a 1 mL syringe, and a drop was squeezed out and dropped on two gold electrodes separated from each other and 0.2 mm apart on the surface of the purchased Al2O3 ceramic plate (1 mm × 1.5 mm), and the drop was repeated 4 times. The fabricated gas sensor was aged at a bias voltage of 4 V for 1 day to obtain a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (4% Sn-doped ZnO).
[0042] Example 2: 1.5mmol ZnO, 0.12mmol SnCl2·2H2O, 3mmol H2BDC and 200μL DMF were put into a nylon ball mill, fixed to a three-dimensional swing ball mill, and ball milled at 1200rpm for 45min. The solid powder in the ball mill was collected to obtain the bimetallic MOF precursor 8% Sn / Zn-MOF-B. It was placed in 30mL DMF solution for ultrasonic treatment for 1 minute. Then, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the DMF solution for ultrasonic treatment, and repeated 3 times. The DMF-treated sample was placed in 30mL ETOH solution for ultrasonic treatment for 5 minutes, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the ETOH solution for ultrasonic treatment, and repeated 3 times. The solvent-treated solid product was dried to obtain a bimetallic MOF precursor 8% Sn / Zn-MOF-L. The prepared 8% Sn / Zn-MOF-L was placed in a ceramic ark, and then the ceramic ark was placed in a tube furnace to heat the MOF precursor in an air atmosphere at a heating rate of 2°C / min. The temperature was raised to 500°C and maintained at 500°C for 150 minutes. After cooling, a single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO) was obtained. 5 mg of 8% Sn-doped ZnO solid powder was taken and put into 0.5 mL ETOH solution, and the dispersion was ultrasonically treated for 30 minutes to form a white suspension. The suspension was aspirated with a 1 mL syringe, and a drop was squeezed out and dropped on two gold electrodes separated from each other and 0.2 mm apart on the surface of the purchased A12O3 ceramic plate (1 mm × 1.5 mm), and the drop was repeated 4 times. The fabricated gas sensor was aged at a bias voltage of 4 V for 1 day to obtain a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO).
[0043] The PXRD diffraction pattern of the bimetallic MOF precursor 8% Sn / Zn-MOF-B obtained in Example 2 is shown in Figure 1 The figure shows that most of the diffraction peaks of the solid sample after ball milling match the standard PXRD peaks of MOF-2, indicating that the precursor MOF structure was successfully synthesized. Figure 2 This is the PXRD spectrum of 8% Sn-doped ZnO prepared in Example 2. The figure shows that the diffraction peaks of the calcined sample correspond to the standard PXRD peaks of hexagonal wurtzite ZnO (JCPDS: 36-1451), and there is no peak of tin oxide, indicating that the doped Sn does not exist as a separate oxide phase. From the XPS spectrum of 8% Sn-doped ZnO (Sn3d spectrum, Figure 3) shows that the Sn element does exist in the oxide structure and exists in a valence state close to +4, indicating that Sn exists in the structure in the form of a single atom. Figure 4 ) and transmission electron microscopy ( Figure 5 ) As can be seen in the figure, the morphology of 8% Sn-doped ZnO is a series of interwoven nanosheets with a diameter of 500-700nm and a thickness of 30-50nm. The gas sensor based on the single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO) was placed in the sensor test system to test the sensing performance of 8% Sn-doped ZnO to acetone gas. Figure 6 It can be seen that the material has the highest response value to 10 ppm acetone at 290 °C, reaching 213 (R a / R g ). Compared with undoped Sn-ZnO, the response value increased by 60%, and the response value remained stable over multiple cycles ( Figure 7 ). At 0.1-30ppm acetone concentration, the response value of the material shows a good linear relationship with the acetone concentration ( Figure 8 ), and the theoretical detection limit of the material for acetone was calculated to be 0.52ppb.
[0044] Example 3: 1.5mmol ZnO, 0.12mmol SnCl2·2H2O, 3mmol H2BDC and 200μL DMF were put into a nylon ball mill, fixed to a three-dimensional swing ball mill, and ball milled at 1200rpm for 45min. The solid powder in the ball mill was collected to obtain the bimetallic MOF precursor 8% Sn / Zn-MOF-B. It was placed in 30mL DMF solution for ultrasonic treatment for 1 minute. Then, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the DMF solution for ultrasonic treatment, and repeated 3 times. The DMF-treated sample was placed in 30mL ETOH solution for ultrasonic treatment for 5 minutes, and centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the ETOH solution for ultrasonic treatment, and repeated 3 times. The solvent-treated solid product was dried to obtain a bimetallic MOF precursor 8% Sn / Zn-MOF-L. The prepared 8% Sn / Zn-MOF-L was placed in a ceramic ark, and then the ceramic ark was placed in a tube furnace to heat the MOF precursor in an air atmosphere at a heating rate of 2°C / min. The temperature was raised to 500°C and maintained at 500°C for 150 minutes. After cooling, a single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO) was obtained. 5 mg of 8% Sn-doped ZnO solid powder was taken and put into 0.5 mL ETOH solution, and the dispersion was ultrasonically treated for 30 minutes to form a white suspension. The suspension was aspirated with a 1 mL syringe, and a drop was squeezed out and dropped on two gold electrodes separated from each other and 0.2 mm apart on the surface of the purchased Al2O3 ceramic plate (1 mm × 1.5 mm), and the drop was repeated 4 times. The gas sensor was aged for 1 day at 4V bias voltage to obtain a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO). The gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO) was placed in a sensor test system, and the response values of 8% Sn-doped ZnO to 10ppm ethanol, methanol, formaldehyde, carbon dioxide, and nitrogen at 290°C were 96.7, 53.2, 23.5, 7.8, and 3.95 ( Fig. 9 ).
[0045] Example 4: 1.5mmol ZnO, 0.18mmol SnCl2·2H2O, 3mmol H2BDC and 200μL DMF were put into a nylon ball mill, fixed to a three-dimensional swing ball mill, and ball milled at 1200rpm for 45min. The solid powder in the ball mill was collected to obtain the bimetallic MOF precursor 12% Sn / Zn-MOF-B. It was placed in a 30mL DMF solution for ultrasonic treatment for 1 minute. Then, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the DMF solution for ultrasonic treatment, and repeated 3 times. The DMF-treated sample was placed in a 30mL ETOH solution for ultrasonic treatment for 5 minutes, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the ETOH solution for ultrasonic treatment, and repeated 3 times. The solvent-treated solid product was dried to obtain a bimetallic MOF precursor 12% Sn / Zn-MOF-L. The prepared 12% Sn / Zn-MOF-L was placed in a ceramic ark, and then the ceramic ark was placed in a tube furnace to heat the MOF precursor in an air atmosphere at a heating rate of 2°C / min. The temperature was raised to 500°C and maintained at 500°C for 150 minutes. After cooling, a single-atom Sn-doped ZnO-based gas-sensitive material (12% Sn-doped ZnO) was obtained. 5 mg of 12% Sn-doped ZnO solid powder was taken and put into 0.5 mL ETOH solution, and the dispersion was ultrasonically treated for 30 minutes to form a white suspension. The suspension was aspirated with a 1 mL syringe, and a drop was squeezed out and dropped on two gold electrodes separated from each other and 0.2 mm apart on the surface of the purchased Al2O3 ceramic plate (1 mm × 1.5 mm), and the drop was repeated 4 times. The fabricated gas sensor was aged at a bias voltage of 4 V for 1 day to obtain a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (12% Sn-doped ZnO).
[0046] Example 5: 2mmol ZnO, 0.16mmol SnCl2·2H2O, 4mmol H2BDC and 267μL of DMF were put into a nylon ball mill, fixed to a three-dimensional swing ball mill, and ball milled at 1200rpm for 45min. The solid powder in the ball mill was collected to obtain the bimetallic MOF precursor 8% Sn / Zn-MOF-B. It was placed in 30mL DMF solution for ultrasonic treatment for 1 minute. Then, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the DMF solution for ultrasonic treatment, and repeated 3 times. The DMF-treated sample was placed in 30mL ETOH solution for ultrasonic treatment for 5 minutes, and centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the ETOH solution for ultrasonic treatment, and repeated 3 times. The solvent-treated solid product was dried to obtain a bimetallic MOF precursor 8% Sn / Zn-MOF-L. The prepared 8% Sn / Zn-MOF-L was placed in a ceramic ark, and then the ceramic ark was placed in a tube furnace to heat the MOF precursor in an air atmosphere at a heating rate of 2°C / min. The temperature was raised to 500°C and maintained at 500°C for 150 minutes. After cooling, a single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO) was obtained. 5 mg of 8% Sn-doped ZnO solid powder was taken and put into 0.5 mL ETOH solution, and the dispersion was ultrasonically treated for 30 minutes to form a white suspension. The suspension was aspirated with a 1 mL syringe, and a drop was squeezed out and dropped on two gold electrodes separated from each other and 0.2 mm apart on the surface of the purchased Al2O3 ceramic plate (1 mm × 1.5 mm), and the drop was repeated 4 times. The fabricated gas sensor was aged at a bias voltage of 4 V for 1 day to obtain a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO).
[0047] Example 6: 3mmol ZnO, 0.24mmol SnCl2·2H2O, 6mmol H2BDC and 400μL DMF were put into a nylon ball mill, fixed to a three-dimensional swing ball mill, and ball milled at 1200rpm for 45min. The solid powder in the ball mill was collected to obtain the bimetallic MOF precursor 8% Sn / Zn-MOF-B. It was placed in 30mL DMF solution for ultrasonic treatment for 1 minute. Then, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the DMF solution for ultrasonic treatment, and repeated 3 times. The DMF-treated sample was placed in 30mL ETOH solution for ultrasonic treatment for 5 minutes, centrifuged at 9000rpm for 4 minutes using a centrifuge to collect the bottom solid. The bottom solid was placed back in the ETOH solution for ultrasonic treatment, and repeated 3 times. The solvent-treated solid product was dried to obtain a bimetallic MOF precursor 8% Sn / Zn-MOF-L. The prepared 8% Sn / Zn-MOF-L was placed in a ceramic ark, and then the ceramic ark was placed in a tube furnace to heat the MOF precursor in an air atmosphere at a heating rate of 2°C / min. The temperature was raised to 500°C and maintained at 500°C for 150 minutes. After cooling, a single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO) was obtained. 5 mg of 8% Sn-doped ZnO solid powder was taken and put into 0.5 mL ETOH solution, and the dispersion was ultrasonically treated for 30 minutes to form a white suspension. The suspension was aspirated with a 1 mL syringe, and a drop was squeezed out and dropped on two gold electrodes separated from each other and 0.2 mm apart on the surface of the purchased Al2O3 ceramic plate (1 mm × 1.5 mm), and the drop was repeated 4 times. The fabricated gas sensor was aged at a bias voltage of 4 V for 1 day to obtain a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material (8% Sn-doped ZnO).
Claims
1. A single-atom Sn-doped ZnO-based gas-sensitive material, characterized in that It is derived from a metal-organic framework and has the morphology of interwoven nanosheets with a diameter of 500-700nm and a thickness of 30-50nm. Sn is doped into the ZnO crystal structure in the form of single atoms during the calcination process, and a large number of evenly distributed Sn active sites are conducive to the adsorption and catalytic decomposition of gas molecules.
2. The single-atom Sn-doped ZnO-based gas-sensitive material according to claim 1, characterized in that The single-atom Sn-doped ZnO-based gas-sensitive material uses zinc oxide powder, divalent tin salt, terephthalic acid, and N,N-dimethylformamide as raw materials, obtains a metal-organic framework precursor through an environmentally friendly mechanochemical method, and then realizes the structural and morphological transformation of the MOF precursor through a simple solvent treatment process, and finally obtains a single-atom Sn-doped ZnO nanosheet through calcination.
3. A method for preparing a single-atom Sn-doped ZnO-based gas-sensitive material, characterized in that The steps include: (1) Synthesis of Sn / Zn-MOF-B: ZnO powder, terephthalic acid, divalent tin salt and N,N-dimethylformamide solvent were mixed and ball-milled into dry and fine white powder to prepare the bimetallic MOF precursor Sn / Zn-MOF-B; (2) Synthesis of Sn / Zn-MOF-L: ① The prepared Sn / Zn-MOF-B was placed in an N,N-dimethylformamide solution, subjected to ultrasonic treatment, centrifuged using a centrifuge, the bottom solid was separated, and then placed in DMF for ultrasonic treatment. The above process was repeated at least 3 times; ② The DMF-treated solid was placed in an ETOH solution, subjected to ultrasonic treatment, centrifuged using a centrifuge, the bottom solid was separated, and then placed in ETOH for ultrasonic treatment. The above process was repeated at least 3 times to obtain the bimetallic MOF precursor Sn / Zn-MOF-L; (3) Synthesis of single-atom Sn-doped ZnO: The prepared Sn / Zn-MOF-L precursor was calcined under air to obtain single-atom Sn-doped ZnO gas-sensitive material.
4. The method for preparing a single-atom Sn-doped ZnO-based gas-sensitive material according to claim 3, characterized in that The molar ratio of Sn to Zn in the solid raw material of step (1) is 2% to 10%; the molar ratio of Zn to H2BDC in the solid raw material of step (1) is 1:1 to 1:2; in step (1), the mass ratio of the solid raw material to the DMF solvent is 3:1 to 2:
1.
5. The method for preparing a single-atom Sn-doped ZnO-based gas-sensitive material according to claim 3, characterized in that In the step (1), ZnO powder, terephthalic acid, divalent tin salt and N,N-dimethylformamide solvent are placed in a ball mill, the ball mill is fixed on a three-dimensional swing ball mill, and ball milling is performed at a rotation speed of 1200 rpm for 40 to 50 minutes.
6. The method for preparing a single-atom Sn-doped ZnO-based gas-sensitive material according to claim 3, characterized in that In the step (2), the prepared Sn / Zn- MOF-B was placed in a DMF solution and subjected to ultrasonic treatment for 1 to 2 minutes; the solution was centrifuged at 8000 to 10000 rpm for 4 to 6 minutes to separate the solid at the bottom, and the solution was re-placed in DMF for ultrasonic treatment, and the process was repeated 3 times; the DMF-treated solid was placed in an ETOH solution and subjected to ultrasonic treatment for 5 to 10 minutes; the solution was centrifuged at 8000 to 10000 rpm for 4 to 6 minutes to separate the solid at the bottom, and the solution was re-placed in ETOH for ultrasonic treatment, and the process was repeated 3 times to obtain a bimetallic MOF precursor Sn / Zn-MOF-L.
7. The method for preparing a single-atom Sn-doped ZnO-based gas-sensitive material according to claim 3, characterized in that In the step (3), the Sn / Zn-MOF-L precursor is placed in a ceramic ark and heated and calcined in a tube furnace; in the step (3), the Sn / Zn-MOF-L precursor is calcined at 450-500° C. for 2-3 hours.
8. A method for preparing a gas sensor based on single-atom Sn-doped ZnO-based gas-sensitive material, characterized in that The steps are as follows: (1) 3-8 mg of single-atom Sn-doped ZnO-based gas-sensitive material is put into 0.5-1 ml of ethanol, and ultrasonic treatment is performed to form a uniform suspension. The suspension is then aspirated and dropped onto two gold electrodes on the surface of an alumina ceramic plate to form a sensor; (2) The sensor drop-casted with the gas-sensitive material is aged for 1 to 3 days in an environment with a bias voltage of 4 V to obtain a gas sensor based on a single-atom Sn-doped ZnO-based gas-sensitive material.
9. Application of a single-atom Sn-doped ZnO-based gas-sensitive material, characterized in that It is used for the detection of trace gases.
10. The use of a single-atom Sn-doped ZnO-based gas-sensitive material according to claim 9, characterized in that The gases are acetone, formaldehyde, methanol and ethanol; acetone, formaldehyde, methanol and ethanol are detected at 270-310°C.
